Deriving C4 photosynthetic parameters from combined gas exchange and chlorophyll fluorescence using an Excel tool: theory and practice. (10th February 2016) - Bellasio, Chandra; Beerling, David J; Griffiths, Howard
Abstract: The higher photosynthetic potential of C4 plants has led to extensive research over the past 50 years, including C4 ‐dominated natural biomes, crops such as maize, or for evaluating the transfer of C4 traits into C3 lineages. Photosynthetic gas exchange can be measured in air or in a 2% Oxygen mixture using readily available commercial gas exchange and modulated PSII fluorescence systems. Interpretation of these data, however, requires an understanding (or the development) of various modelling approaches, which limit the use by non‐specialists. In this paper we present an accessible summary of the theory behind the analysis and derivation of C4 photosynthetic parameters, and provide a freely available Excel Fitting Tool (EFT), making rigorous C4 data analysis accessible to a broader audience. Outputs include those defining C4 photochemical and biochemical efficiency, the rate of photorespiration, bundle sheath conductance to CO2 diffusion and the in vivo biochemical constants for PEP carboxylase. The EFT compares several methodological variants proposed by different investigators, allowing users to choose the level of complexity required to interpret data. We provide a complete analysis of gas exchange data on maize (as a model C4 organism and key global crop) to illustrate the approaches, their analysis and interpretation. © 2015 John Wiley & Sons Ltd Abstract : We present an accessible summary of the theory behind the analysis and derivation of C4 photosynthetic parameters, and provide a freely available Excel Fitting Tool (EFT), making rigorous C4 data analysis accessible to a broader audience. A complete analysis of gas exchange data is exemplified on maize (as a model C4 organism and key global crop) to illustrate the approaches, their analysis and interpretation.